2021
DOI: 10.1364/ao.419800
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of YAG:Ce phosphor dosimeter by the co-precipitation method for radiotherapy

Abstract: Yttrium aluminum garnet (YAG) doped with Ce was synthesized via the co-precipitation method with N H 4 H C O 3 as the precipitant. The spectroscopic properties and the effects of the Ce doping concentration and sintering atmosphere on the crystal phase were investigated. The dosimeter of YAG:Ce phosphor material was prepared to study the radioluminescence (RL) characteristics of a clinical linear accelerator. A satisfying linear relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…In previous studies [26,27], it was found that sintering samples under nitrogen atmosphere obtains better results, so a nitrogen atmosphere was selected when the samples in this paper were prepared. At the same time, the XRD spectrum of samples sintered at different temperatures showed a slight difference, as shown in Figure 3.…”
Section: Characterization Of Xrdmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies [26,27], it was found that sintering samples under nitrogen atmosphere obtains better results, so a nitrogen atmosphere was selected when the samples in this paper were prepared. At the same time, the XRD spectrum of samples sintered at different temperatures showed a slight difference, as shown in Figure 3.…”
Section: Characterization Of Xrdmentioning
confidence: 99%
“…Meanwhile, the sol-gel method is more friendly and simpler to generate solid metal oxides with even better chemical uniformity. The doping concentration and sintering atmosphere determine the materialized properties of the powder to a great extent, and in earlier work, we studied the luminescence and radiation characteristics of the powder material by the coprecipitation method [26] and sol-gel method [27], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The ions Tb 3+ and Mn 2+ have both been employed as green and red radiation elements in the past. Owing to the prohibited 4f-4f shift for Tb 3+ as well as 4 T1-6 A1 transitions for Mn 2+ , the excitation bands of Tb 3+ as well as Mn 2+ ions between ultraviolet (UV) and the area that is possible to be seen, are very faint [14], [15]. A common way to increase the absorption of Tb 3+ and Mn 2+ in the UV region would be using an effective sensitizer, like Ce 3+ , and transfer the forcefully absorbed stimulation power from 5d level of Ce 3+ to level of 5 D3,4 Tb 3+ or 4G level of Mn2+'s [11], [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…Several silicate phosphors have become a subject of research owing to the feature of high stability in chemical and thermal performances, as well as providing low production cost. Thus, the rare-earth ions have been widely doped into the silicate host lattice to amplify the performance of these phosphors [8], [9]. 2% concentration of Mn 2+ ion was doped with Ca2SiO4 phosphor and resulted in broad emission bands from 450 to 600 nm, with two emission peaks at 475 nm and 550 nm [10], 2574 [11].…”
Section: Introductionmentioning
confidence: 99%